The worldview of pre-service and in-service teachers about health education - Špernjak, Andreja; Šorgo, Andrej (Revija za elementarno izobraževanje, 2020)
Health is coconsidered as goodness; therefore, schools should be places where healthy habits, along with evidence-based medical knowledge and practices, are taught and practised. The key persons in education are teachers, so their opinions and worldviews should not be neglected. The objective of this work was to identify opinions about health education among Slovenian teachers. We investigated the worldviews of and differences between pre-service and in-service Biology teachers about health education. The questionnaires were delivered to 163 Sloveian participants. Most differences in opinion occurred in the nutrition field between younger and older participants. The majority of participants (85%) agree that “Providing knowledge or developing behavior that is respectful of one´s own health” is the main goal of health education.